Occurrence of pharmaceuticals in the environmental waters: African and Asian perspectives - Ngwako Joseas Waleng; Philiswa Nosizo Nomngongo (Environmental Chemistry and Ecotoxicology, 2022)
Environmental ubiquity of pharmaceuticals has stimulated a lot of societal and global concerns. The occurrence of pharmaceuticals in the environment differs from country to country depending on the extent of consumption and monitoring. Most studies reporting the occurrence of pharmaceuticals are conducted in coastal regions with numerous articles and reviews reported in developed countries. The current review reports the occurrence of pharmaceuticals in inland waters with major focus devoted to developing countries in Africa and Asia. The focus was further dedicated to sources and distribution mechanisms, which contribute greatly to their ubiquity in the environment. Antibiotics and non-steroidal anti-inflammatory drugs (NSAIDs) are the most reported pharmaceuticals in African waters. For example, an antibiotic (sulfamethoxazole) was detected in more than four African countries with highest concentrations reaching 53.8–56.6 μg L−1 detected in Kenya and Mozambique. Furthermore, highest concentrations of amoxicillin ranging from 0.087–272.2 μg L−1 were detected in Nigeria. Ibuprofen, which is NSAID was detected at highest concentrations reaching 67.9 and 58.7 μg L−1 in Durban city and Msunduzi River (KwaZulu-Natal, South Africa), respectively. However, highest concentration of antiretroviral drug (lamivudine) up to 167 μg L−1 was found in surface water samples collected from Nairobi and Kisumu city, Kenya. In Asian countries, antibiotics were detected at highest concentration reaching 365.05 μg L−1 in surface water samples. However, concentrations of other pharmaceuticals were comparably below the concentrations detected in African environmental waters. Health risks associated with their fate in the environment are critically reviewed. Sample preparation techniques and analytical instruments necessary for the occurrence studies were also reviewed. The concluding remarks were based on deliberating the possible future prospects within the research expertise.